Analisis Return Saham Perusahaan Industri Dasar dan Kimia yang Terdaftar di BEI - Irine Hesti Kusumaningdinni; Nurjanti Takarini (Jurnal Dinamika Ekonomi & Bisnis, 2021)
When people invest, they can be obtained some retribution, we know that stock returns. The study aims to determining the effects of solvability, profitability, market value on stock returns of basic industry and chemicals based on the Indonesia Stock Exchange for the period of 2017 to 2019. The research approach purposive sampling method, so 45 companies were obtained from 60 basic industry and chemicals companies that based on the Indonesia Stock Exchange. The author approach quantitative data in the form of financial report obtained through in Indonesia Stock Exchange. The author used multiple regression analysis research method. The result showed that solvability has a positive and significant effect on stock returns, profitability has a positive and significant effect on stock returns, and market value has a positive and significant effect on stock returns of basic industry and chemical companies that based on the Indonesia Stock Exchange.